High-Intensity Interval Training Improves Markers of Oxidative Metabolism in Skeletal Muscle of Individuals With Obesity and Insulin Resistance - Matos, Mariana Aguiar de; Vieira, Dênia Vargas; Pinhal, Kaio Cesar; Lopes, Jennifer Freitas; Dias-Peixoto, Marco Fabrício; Pauli, José Rodrigo; Castro Magalhães, Flávio de; Little, Jonathan P.; Rocha-Vieira, Etel; Amorim, Fabiano Trigueiro (Frontiers in Physiology, 2018)
Background: The excess body fat characteristic of obesity is related to various metabolic alterations, which includes insulin resistance. Among the non-pharmacological measures used to improve insulin sensitivity are aerobic physical training, such as high intensity interval training (HIIT). This study investigated the effects of 8 weeks of HIIT on blood and skeletal muscle markers related to insulin resistance (IR) and oxidative metabolism in physically inactive individuals with obesity and compared the changes between insulin resistant and non-insulin resistant phenotypes. Methods: Nine non-insulin (OB) and eight insulin-resistant (OBR) volunteers with obesity completed 8 weeks of HIIT in a cycle ergometer. Venous blood and vastus lateralis muscle samples were obtained before and after the HIIT. Body composition and peak oxygen consumption (VO2peak) were estimated before and after HIIT. Results: HIIT reduced IR assessed by the homeostatic model assessment of insulin resistance (HOMA-IR) in OBR (4.4 ± 1.4 versus 4.1 ± 2.2 (mmol) (μU)/l2), but not in OB (HOMA-IR 1.8 ± 0.5 versus 2.3 ± 1.0 (mmol) (μU)/l2) volunteers. HIIT increased VO2peak with no change in body fat in both groups. In skeletal muscle, HIIT increased the phosphorylation of IRS (Tyr612), Akt (Ser473), and increased protein content of β-HAD and COX-IV in both groups. There was a reduction in ERK1/2 phosphorylation in OBR after HIIT. Conclusion: Eight weeks of HIIT improved markers of the insulin signaling pathway and increased the content of proteins related to oxidative metabolism in skeletal muscle of individuals with obesity, independent of changes in insulin resistance or total body fat.